Collins COBUILD advanced dictionary of American English - Cobuild, Collins (Thomson Heinle, 2007)
With innovations such as DefinitionsPLUS and vocabulary builders, the Collins COBUILD Advanced Dictionary of American English transforms the learner's dictionary from an occasional reference into the ultimate resource and must-have dictionary for language learners. The definitions have been created using a controlled vocabulary, and each definition has been reviewed by a team of classroom teachers to ensure that they are appropriate for learners at the intermediate level